Model Kepemimpinan Kepala Sekolah dalam Meningkatkan Kinerja Guru Di Madrasah Tsanawiyah Negeri 1 Bone - Fitri .; Nurlina . (JURNAL MAPPESONA, 2025)
This study was conducted with the aims: to identify and examine the principal's leadership model, to identify and examine the principal's leadership behavior, to understand and to examine the methods used by the principal to improve teacher performance. This research is a field research with qualitative research methods. The approach used is a behavioral and contingency approach. Data were collected using questionnaires, observation guidelines, interviews and documentation. Testing the validity of the data in this study using persistent observation techniques and triangulation techniques. The results of the analysis of the data obtained indicate that the principal's leadership model affects the performance produced by teachers at MTsN 1 Bone. The Situational Model applied at MTsN 1 Bone has an effect on teacher performance in the form of work motivation and enthusiasm for work.